Efektivitas E-Modul Fisika SMA Terintegrasi Materi Kebakaran Berbasis Model Problem Based Learning - Agustia, Frima Suci; Fauzi, Ahmad (Universitas Negeri Padang, 2020)
Learning is expected to use a variety of learning resources, can increase the independence and activeness of students and based on the potential of the region so that students have the ability to recognize and understand the characteristics of the area. The reality found in the field shows that the teacher has not used the learning model so that students are not too active in learning, learning resources used are only in the form of textbooks, and the material has not been integrated into the regional potential. Based on the analysis of regional potentials, it shows that West Sumatra is a disaster-prone area, one of which is fire. To implement the knowledge of disaster requires a means that can present the disaster clearly, namely in the form of non-printed teaching materials, one of which is e-module. The purpose of this study is to produce an integrated e-module of high school physics in fire material based on an effective Problem Based Learning model. This type of research is research and development using the Plomp model which consists of 3 stages of research, namely preliminary research, development or prototyping phase, and assessment phase. The research instrument was a descriptive test consisting of 25 multiple choice questions. The data analysis technique used the N-Gain formula. The results showed that the use of e-module physics integrated high school fire material based on problem based learning models was effective to improve the competence of students including knowledge with an N-Gain value of 0.75 in the high category.